Characterization and properties of gamma irradiated epoxidized natural rubber latex - Chai, Chee Keong (2020)
Epoxidized natural rubber latex (ENRL) is the liquid form of epoxidized natural rubber (ENR), which possesses many enhanced properties that are lacking in its unmodified origin, i.e. natural rubber latex. Despite extensive literature on the studies and applications of ENR, very limited work done on ENRL to understand and exploit commercial applications of this material. In relation to this, it is important to test the hypothesis that properties of ENRL can be improved by means of gamma irradiation. Hence, a study was conducted to determine the effect of gamma irradiation on ENRL, the effect of sensitizer on ENRL during gamma irradiation and the effect of antioxidant on gamma irradiated ENRL. The novelty of this study is the utilization of gamma radiation for crosslinking of ENRL. ENRL with 25 mol% (ENRL-25) and 50 mol% (ENRL-50) epoxidation level was used in this study. The sensitizers were n-butyl acrylate (n-BA), 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate (TMPTA). The antioxidant was 4,6-bis (octylthiomethyl)-o-cresol (Irganox 1520). Gamma radiation ranged from 0 to 160 kGy. Cast films were prepared from the gamma irradiated ENRL and used for characterization via tensile test, gel fraction test, aging test, Fourier transform infrared analysis (FTIR), dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA). Results revealed that gamma irradiation is capable of inducing crosslinks in ENRL-25 and ENRL-50, with an optimum dose and tensile strength of 80 kGy and 5.4 – 6 MPa respectively. The effect of gamma irradiation is more prominent on ENRL-25 than ENRL-50 due to higher quantity of unreacted carbon-carbon double bonds (C=C) in the former. Dynamic mechanical properties of gamma irradiated ENRL showed significant positive shift in glass transition temperature (Tg) of tan delta and loss modulus. Effect of gamma irradiation on thermal properties of ENRL-25 is negligible, whereas its effect on ENRL-50 is positive but marginal. The presence of sensitizer gives positive impact on gamma irradiation of ENRL. The impact increases in the order of n-BA < HDDA < TMPTA. The effect of sensitizer on ENRL-25 is higher than ENRL-50 due to the presence of more C=C in ENRL-25. The tensile strength of gamma irradiated ENRL with sensitizer are lower than those without sensitizer, suggesting that physical chain entanglement prevails chemical crosslink in the former. The presence of sensitizer in gamma irradiated ENRL enhances its thermal stability. Their effect on thermal stability increases in the order of TMPTA < HDDA < n-BA. Irganox 1520 is effective in enhancing the resistance of gamma irradiated ENRL against thermo-oxidative degradation. However, it inhibits the efficiency of radiation-induced crosslinking due to radical scavenging effect. ENRL-50 shows better heat resistance than ENRL-25 due to the presence of more epoxide groups in the former that resulted more ether crosslinks in the former. Based on experimental findings, ENRL-25 and ENRL-50 are crosslinkable by gamma radiation, thus, their mechanical, dynamical and thermal aging properties can be improved by means of gamma irradiation.